Model Rancangan Campuran Kerja Campuran Panas Agregat â Buton Epure - Perpustakaan UGM, i-lib ([Yogyakarta] : Department of Chemistry Gadjah Mada University, 2000)
The hot mix asphalt (HMA) consists of course and fine aggregates, filler and asphalt. Due to increasing traffic demand, high performance of HMA is needed. In order to fulfill the demand, The Asphalt Institute introduces a model of formula which is called Superpave. The model is based on air voids target of 4 % as the mean of air voids limit, and therefore a long life service will be exhibited by the HMA layer. It is known that there is a large deposit of rock asphalt in Buton island. By an extraction process, bitumen and filler can be found, and after an improvement both can be mixed on a certain composition which is called Buton Epure. The Buton Epure can be employed as a material of HMA. In practice, field engineers need job mix formulas, so such models will be useful. Based on the model of Superpave, a job mix formula of hot mix aggregate â Buton Epure can be established. In this research BE 55 PG was employed as a binder, indicate that the job mix formula model of hot mix aggregate â Buton Epure worked well and a job mix formula of 4.05 % air voids, which is closed to air voids target.